Análisis del impacto de la integración fotovoltaica en los sistemas de iluminación - Andrango Quilumbaquin, Geovanny Germán (2022)
In the present research project, the analysis of photovoltaic integration in lighting systems is carried out through laboratory measurements and simulations in DIALux Evo and ETAP 20.1 software, applying standards such as: Regulation No. ARCERNNR 006/20, ARCONEL 003/18, IEEE Standard 519-2014, IEC Standard 61000-3-2, among others. In the first instance, bibliographic research was carried out on photovoltaic integration in lighting systems. Subsequently, information was sought on the georeferenced plan of the central park of the Tanicuchi parish with real measurements, a 150 W LED lamp was installed to obtain luminosity data with the lux meter and disturbances with the network analyzer. Then three case studies were proposed that consist of designing the LED lighting system in the DIALux Evo software, sizing of the photovoltaic system connected to the grid capable of covering the demand generated by the system and the analysis of disturbances in the ETAP 20.1 software. In addition, solutions are proposed to mitigate disturbances generated by LED lamps.